FORECASTING MANILA SOUTH HARBOR MEAN SEA LEVEL USING SEASONAL ARIMA MODELS - Q. Fernandez, Flerida Regine; Montero, Neil B.; Po III, Rodolfo B.; Addawe, Rizavel C.; Diza, Hazel Mae R. (Journal of Technology Management and Business, 2018)
Global warming has adverse effects which include the rise of the mean sea level. This could be a problem especially those countries that are surrounded by bodies of water. The Manila South Harbor is a part of the South China Sea being one of the bodies of water that surround the Philippines. This paper aims to find Seasonal Autoregressive Integrated Moving Average (SARIMA) models that fits the given time series composed of the mean sea level of the Manila South Harbor from 2008 to 2014 measured in millimeters. Results show that there are three possible models that fit the time series but the chosen one is the model SARIMA. The forecasted values were then compared to the actual values of the mean sea level for the year 2015.